Concordia Station, Dome C, Antarctica as a Ground-Based Analog for Spaceflight/Planetary Exploration: The CHOICE* Immunology Study - Mehta, Satish; Salam, Alex; Sams, Clarence; Rybka, Alex; Chouker, Alexander; Stowe, Raymond; Quiriarte, Heather; Pierson, Duane; Crucian, Brian (2012)
No abstract available